Isolation of a sheep - embryo after oestrus synchronisation - Τσερνενές Ν.; Λαλιώτης Β.; Ποΐλας Σ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The Center of Artificial Insemination and Reproductive Diseases of Athens pursuing the embryotraslantation in the productive Animals began an experimental work of the whole subject. Subject of the this study was, as a first step, the isolation of sheep - embryo. The research was done in two sheep - hydrld after synchromistation of oestrus by PMSG and prostaglandin. The isolation of the embryos was achieved by repeated washings of the horns of uterus with Dulbecco’ s solution after laparotomy at seventh days post inoculation of P.M.S.G. The washinliquide were examined at the steroscope, one embryo was isolated and after was photographed. The embryo was at the stage of morula which coinsides to the 5t h day of the natural mating.